Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x2 - x - 6
= x2 + 2x - 3x - 6
= x(x + 2) - 3(x + 2)
= (x + 2)(x - 3)
b) 27x3 + 6x2 - 2x - 1
= 27x3 - 1 + 6x2 - 2x
= (3x - 1)(9x2 + 3x + 1) + 2x(3x - 1)
= (3x - 1)(9x2 + 3x + 2x + 1)
= (3x - 1)(9x2 + 5x + 1)
d) x2 - 16x - 17
= x2 + x - 17x - 17
= x(x + 1) - 17(x + 1)
= (x + 1)(x - 17)
e) x4 - 5x2 + 6
= x4 - 2x2 - 3x2 + 6
= x2(x2 - 2) - 3(x2 - 2)
= (x - căn 2)( x + căn 2)(x - căn 3)( x + căn 3)
g) 9(x - 1)2 - 16(x + 1)2
= 32(3x - 1)2 - 42(x + 1)2
=(9x - 3)2 - (4x + 4)2
= (9x - 3 - 4x - 4)(9x - 3 + 4x + 4)
= 13x(5x - 7)
Rút gọn các phân thức:
a) \(\frac{\left(3x+2\right)^2-\left(x+2\right)^2}{x^3-x^2}=\frac{9x^2+12x+4-x^2-4x-4}{x^3-x^2}=\frac{8x^2+8x}{x^3-x^2}=\frac{8x\left(x+1\right)}{x^2\left(x-1\right)}=\frac{8\left(x+1\right)}{x-1}\)
b) \(\frac{x^4-1}{x^3+2x^2-x-2}=\frac{\left(x^2-1\right)\left(x^2+1\right)}{\left(x^3-x\right)+\left(2x^2-2\right)}=\frac{\left(x^2-1\right)\left(x^2+1\right)}{\left(x+2\right)\left(x^2-1\right)}=\frac{x^2+1}{x+2}\)
c) \(\frac{x^2+7x+12}{x^2+5x+6}=\frac{\left(x^2+3x\right)+\left(4x+12\right)}{\left(x^2+3x\right)+\left(2x+6\right)}=\frac{\left(x+3\right)\left(x+4\right)}{\left(x++3\right)\left(x+2\right)}=\frac{x+4}{x+2}\)
d) \(\frac{x^{10}-x^8+x^6-x^4+x^2-1}{x^4-1}=\frac{\left(x^{10}-x^8\right)+\left(x^6-x^4\right)+\left(x^2-1\right)}{\left(x^2-1\right)\left(x^2+1\right)}=\frac{\left(x^2-1\right)\left(x^8+x^4+1\right)}{\left(x^2-1\right)\left(x^2+1\right)}=\frac{x^8+x^4+1}{x^2+1}\)
a) (x - 2)(x + 2)(x2 + 4) - (x2 - 3)(x2+3)
= (x2 - 4)(x2 + 4) - (x2 - 3)(x2+3)
= x4-16-x4+9
= -7
a: \(125-x^6=\left(5-x^2\right)\left(5+5x^2+x^4\right)\)
b: \(=\left(x^2+1-3\right)^2=\left(x^2-2\right)^2\)
c: \(=\left(3x+15\right)^2-\left(x+7\right)^2\)
\(=\left(3x+15+x+7\right)\left(3x+15-x-7\right)\)
\(=\left(4x+22\right)\left(2x+8\right)\)
\(=2\left(2x+1\right)\left(x+4\right)\)
d: \(=9-\left(x-y\right)^2\)
\(=\left(3-x+y\right)\left(3+x-y\right)\)
e: \(=x\left(x^2+2xy+y^2-9\right)\)
\(=x\left(x+y-3\right)\left(x+y+3\right)\)
1) \(x^2+x-2=0\)
\(\Leftrightarrow x^2+2x-x-2=0\)
\(\Leftrightarrow x\left(x+2\right)-\left(x+2\right)=0\)
\(\Leftrightarrow\left(x+2\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=1\end{cases}}\)
2) \(x^2+2x-3=0\)
\(\Leftrightarrow x^2+3x-x-3=0\)
\(\Leftrightarrow x\left(x+3\right)-\left(x+3\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=1\end{cases}}\)
3) \(x^2-x-6=0\)
\(\Leftrightarrow x^2-3x+2x-6=0\)
\(\Leftrightarrow x\left(x-3\right)+2\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x+2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=3\\x=-2\end{cases}}\)
4) \(x^2+x-6=0\)
\(\Leftrightarrow x^2+3x-2x-6=0\)
\(\Leftrightarrow x\left(x+3\right)-2\left(x+3\right)=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=2\end{cases}}\)
5) \(2x^2-x-6=0\)
\(\Leftrightarrow2x^2-4x+3x-6=0\)
\(\Leftrightarrow2x\left(x-2\right)+3\left(x-2\right)=0\)
\(\Leftrightarrow\left(x-2\right)\left(2x+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-\frac{3}{2}\end{cases}}\)
Câu 2 sai đề nhé
Phải là:(x-999)/99+(x-896)/101+(x-789/103)=6
\(=-x^2-x+2\)